Innovative Industrial Clusters in the Context of Digitalization and Sustainable Competitiveness - A. Salimova, Tatiana; D. Guskova, Nadezhda; N. Krakovskaya, Irina; I. Biryukova, Lyudmila (International Journal of Criminology and Sociology, 2022)
To ensure Russia's sustainable competitiveness, it is necessary to create an infrastructure that allows creating globally competitive technologies and products. The authors suggest that industrial clusters can drive the country’s sustainable economic and innovative development. The research methodology is based on the content of the concept of sustainable competitiveness and cluster theory. The study was carried out using the methods of regression analysis. The systematization of foreign and Russian researchers’ ideas contribute to the conclusion that the cluster approach for ensuring sustainable development and competitiveness in the digital era is regarded as absolutely reasonable. In order to test the hypothesis of the study using regression analysis, a model has been built to assess the dependence and influence of the number of clusters in Russia Federal Districts on the main indicators of economic innovative development of these territories. The regression models constructed by the authors demonstrate a clear dependence of region economic and innovative development indicators on the clustering level. The authors of the present research recognize that clustering should be considered one of the basic elements in the system of national and regional sustainable competitiveness.